Dichotomy between T Cell and B Cell Tolerance to Neonatal Retroviral Infection Permits T Cell Therapy - Mavrommatis, Bettina (AAI, 2016)
Elucidation of the immune requirements for control or elimination of retroviral infection remains an important aim. We studied the induction of adaptive immunity to neonatal infection with a murine retrovirus, under conditions leading to immunological tolerance. We found that the absence of either maternal or offspring adaptive immunity permitted efficient vertical transmission of the retrovirus. Maternal immunodeficiency allowed the retrovirus to induce central Th cell tolerance in the infected offspring. In turn, this compromised the offspring’s ability to mount a protective Th cell–dependent B cell response. However, in contrast to T cells, offspring B cells were not centrally tolerized and retained their ability to respond to the infection when provided with T cell help. Thus, escape of retrovirus-specific B cells from deletional tolerance offers the opportunity to induce protective retroviral immunity by restoration of retrovirus-specific T cell help, suggesting similar T cell immunotherapies for persistent viral infections.